Study on removal of oxytetracycline hydrochloride in marine aquaculture wastewater by Zn0.75Mn0.75Fe1.5O4/ZnFe2O4/ZnO photocatalyst. (25th May 2021) - Li, Zejun; Yu, Xiaocai; Fu, Jiayuan; Zhang, Yongxia; Xue, Bining; Liu, Jinghua
Abstract: Photocatalytic degradation of oxytetracycline hydrochloride (OTC‐HCl) in marine aquaculture wastewater and therefore the effects of factors on the effectiveness of photocatalysts are studied in this paper using Zn0.75 Mn0.75 Fe1.5 O4 /ZnFe2 O4 /ZnO under visible light and changing the molar ratio of Zn 2+ :Fe 3+ :Mn 2+, calcination temperature of catalysts, hydrogen peroxide concentration, dose of catalysts, illumination time of photocatalytic and initial concentration of OTC‐HCl. The degradation of OTC‐HCl in marine aquaculture wastewater was optimized by orthogonal experiment. The best effect exists when the molar ratio of Zn 2+ :Fe 3+ :Mn 2+ was 10:1:3, the calcination temperature of photocatalyst was 400°C, the concentration of hydrogen peroxide was 0.5 g/L, the dose of catalysts was 0.6 g/L, the illumination time was 2.5 h and the initial concentration of OTC‐HCl was 0.010 g/L. The degradation rate of OTC‐HCl can reach 80.18%. Zn0.75 Mn0.75 Fe1.5 O4 /ZnFe2 O4 /ZnO can effectively degrade the OTC‐HCl in marine aquaculture wastewater under visible light.